(untitled) (Research, Society and Development, 2023)
Introduction: Birth is a physiological and natural event, which adds several cultural meanings and, therefore, is a remarkable moment in a woman’s life. Objective: To understand the perception of women about birth in a low-risk maternity ward during the COVID-19 pandemic. Methods: Qualitative study composed of 18 puerperal women who had vaginal delivery during the COVID-19 pandemic assisted by obstetric nurses. Conducted between September and November 2021 in a public maternity hospital in the state of Pernambuco, a reference for pregnant women at habitual risk. The content analysis was made from interviews that followed a semi-structured script, transcribed in a reliable way, and through data extracted from the prenatal card. Questions were asked about obstetric characteristics, labor and the feeling of being pregnant/parturient in the pandemic. This research followed all the recommendations of the Research Ethics Committee. Results: Multiparous puerperas, with a mean age of 27.8 (± 6.9) years, the color of brown skin prevailed, with residence in the urban area, with a partner and paid work, half had a family income of 1 salary. The analysis of clinical qualitative content revealed two categories: 1) Guidelines and measures to cope with SARS-CoV-2; 2) Feelings of parturients regarding giving birth in a pandemic. Conclusion: There was a negative impact regarding psychological factors, such as fear and insecurity, due to the fear of contracting the virus and developing possible complications. However, in childbirth care, many alterations were not evidenced, besides the use of masks and social distancing.